2018
DOI: 10.3390/genes9030167
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Alteration of the Gut Microbiome and Its Impact on Weight and Fat Mass: A Systematic Review and Meta-Analysis

Abstract: Dietary alteration of the gut microbiome is an important target in the treatment of obesity. Animal and human studies have shown bidirectional weight modulation based on the probiotic formulation used. In this study, we systematically reviewed the literature and performed a meta-analysis to assess the impact of prebiotics, probiotics and synbiotics on body weight, body mass index (BMI) and fat mass in adult human subjects. We searched Medline (PubMed), Embase, the Cochrane Library and the Web of Science to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 62 publications
9
82
1
2
Order By: Relevance
“…Our further study revealed that amelioration of PCOS phenotype including hormonal disturbance may closely associated with the reduction of inflammation and the alteration of gut microbiota. In this paper, dietary inulin and metformin were demonstrated to possess capacity to alleviate PCOS throughout a series of routine indicators including pathological examination, reduced BWs, as well as rectification of abnormal hormones (T and E2), which were consistent with previous studies [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Our further study revealed that amelioration of PCOS phenotype including hormonal disturbance may closely associated with the reduction of inflammation and the alteration of gut microbiota. In this paper, dietary inulin and metformin were demonstrated to possess capacity to alleviate PCOS throughout a series of routine indicators including pathological examination, reduced BWs, as well as rectification of abnormal hormones (T and E2), which were consistent with previous studies [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Bir derleme çalışmasının sonuçlarında, gut mikrobiyotasının bazı diyetsel ajanlarla modülasyonu sonucunda plaseboya kıyasla kontrol grubunun vücut kilosu, yağ kütlesi ve BKİ gibi parametlerinde belirgin oranda azaldığı ve bu tür müdahalelerin obezitenin tedavisinde önemli bir etken olarak rol alabileceği vurgulanmıştır. 38 Ancak, probiyotik tüketiminin BKİ üzerine olan etkilerini araştıran çift kör 19 çalışmayı değerlendiren bir meta-analizde, vücut ağırlığında 0,54 kg ve BKİ'de 0,49 kg/m 2 'lik anlamlı düzeyde bir azalma olmasına rağmen, BKİ'de anlamlı bir değişim için birden fazla probiyotik türün sekiz hafta ve daha uzun süre ile kullanılması gerektiği bildirilmiştir. 39 Başka bir çalışmada, 87 bireyin 12 hafta süre ile günde 200 gr probiyotikle zenginleştirilmiş fermente süt ve kontrol süt tüketim sonucunda abdominal yağlanma ve subkütan yağ alanında, vücut ağırlığında, bel ve kalça çevresi ölçümlerinde anlamlı azalmanın yanı sıra BKİ'de %1,8'lik bir düşme saptanmıştır.…”
Section: Discussionunclassified
“…Further a longer period of probiotics use even with low dose =>significant decrease of both weight and BMI. Thus Wang et al, 74 concluded that use of dietary agents for modulating gut microbiota was an essential tool for treatment of obesity. 74 Yet different conclusions got drawn by Drer et al in another meta-analysis, where RCTs and crossover trials were taken into account and results were stratified by age.…”
Section: Role Of Synbioticsmentioning
confidence: 99%
“…Thus Wang et al, 74 concluded that use of dietary agents for modulating gut microbiota was an essential tool for treatment of obesity. 74 Yet different conclusions got drawn by Drer et al in another meta-analysis, where RCTs and crossover trials were taken into account and results were stratified by age. 75 Studies involving pregnant women with term babies, neonates and individuals having GIT problems which might mask the effect of gut microbiota modulation were excluded.…”
Section: Role Of Synbioticsmentioning
confidence: 99%